Historical and Current Perspective of Yoga: An Overview. - Kapil; Pandey, Ajai Kumar; Chowdhury, Kanchan; Sonika (International Research Journal of Ayurveda & Yoga, 2023)
Traditional Yoga practices have been mentioned since the era of Indus Valley Civilization, Vedic & Upanishad heritage, Buddhist and Jain traditions. Shiva is regarded as the first yogi in ancient Yoga tradition. The science of Yoga has been traced since long before the first religions or belief systems were born. At that time Yoga was practiced under the influence of nature under the guidance of the Gurus and its spiritual value was given special importance. In ancient times Yoga was known only for its spirituality to achieve highest level of consciousness. Today Yoga is not meant for spirituality only but it acquires the wider dimension by inculcating physical, mental and social aspect of health of healthy person. Newer evidence shows that Yogic Practices are gaining momentum for its therapeutic application for the management of health related issues of body and mind. Now-a-days Yoga education and its practices are being impacted by many eminent Yoga clinics, Yoga therapy and Wellness centers that have been established, medical institutes and therapeutic setups. People take up Yoga practice to maintain their health and lifestyle.